2016
DOI: 10.1007/s10812-016-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Energy Denominator Shift Parameter of KRb Electronic States in Quantum Chemical Computations Using Perturbation Theory

Abstract: The infl uence of the energy denominator shift (EDS) parameter and the quantitative and qualitative compositions of electronic states included in CASSCF(2,14)/XMCQDPT2 ab initio calculations of the ground state equilibrium internuclear distance and dissociation energy of polar KRb was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The calculated TDMs for the transitions from the ground state to the all spin-mixed excited states with the DX = 0, ±1 selection rules as the functions of internuclear distances are shown in 8), (6)1/2 ( 9), (7)1/2 (10), and (4)3/2 (11). limit II are nonzero in conformity with the selection rules for the atomic transitions.…”
Section: Electronic Statesmentioning
confidence: 60%
See 2 more Smart Citations
“…The calculated TDMs for the transitions from the ground state to the all spin-mixed excited states with the DX = 0, ±1 selection rules as the functions of internuclear distances are shown in 8), (6)1/2 ( 9), (7)1/2 (10), and (4)3/2 (11). limit II are nonzero in conformity with the selection rules for the atomic transitions.…”
Section: Electronic Statesmentioning
confidence: 60%
“…Recently [11,12] we have shown that the ab initio calculations at the CASSCF/XMCQDPT2 (Extended Multi-Configuration Quasi-Degenerate 2nd Order Perturbation Theory) [13] level of theory predict the spectroscopic parameters of the ground state for the KRb molecule with a high accuracy. For the dissociation energy D e of the ground X 1 R + state, we have 4213.1 cm À1 that is in a better agreement with the experimental value (4217.815 cm À1 [14]) than those in other ab initio calculations (for details see [12]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain more reliable energies XMCQDPT2 method [16] was used. All the eight lowest double occupied orbitals were involved in the perturbation calculations, the ISA shift [21] of 0.190 [22] being used. The dimensions of the effective Hamiltonian were 11 Â 11 and 5 Â 5 for doublet and quartet states, respectively.…”
Section: Computationsmentioning
confidence: 99%
“…All eight lowest double occupied orbitals were included in the perturbation based calculations. The ISA shift of 0.20 [47,48] was used in present approach. The dimension of the effective Hamiltonian was 13 Â 13 [48].…”
Section: Computationsmentioning
confidence: 99%